Discovery Of New Potential Pyrido[2,3-D]Pyrimidin-7-One Based Cdk4 Inhibitors Using Molecular Modelling Approaches - Al Attraqchi, Omar Husham Ahmed (2023)
Cyclin-dependent kinases (CDKs) are a class of regulatory enzymes that modulate various biochemical properties of the cell such as cell division. Different CDK enzymes have been shown to be promising biological targets for combating different types of cancer. In particular, the CDK4 enzyme has been observed to be overexpressed in several types of cancer including breast cancer. The usage of small-drug molecules that inhibits the activity of the CDK4 enzyme has proved to be clinically valid approach. However, currently available solutions suffer from various limitations such as insufficient activity. Among the most notable inhibitors of the CDK4 enzyme are the compounds based on the pyrido[2,3-d]pyrimidin-7-one scaffold. In this study, computer-aided drug design (CADD) methods including ligand-based and structure-based methods have been applied on the compounds derived from this scaffold. The applied CADD methods revealed the correlation of the physicochemical properties with the activity and gave insights into the binding process. The used ligand-based CADD methods included quantitative structure-activity relationship (QSAR) and pharmacophore modeling.